Ulun Danu Beratan Temple as an Economic Contest Arena in a Multicultural Society - Gede Mahardika; Ketut Suda; I Wayan Winaja (UNHI PRESS, 2022)
Ulun Danu Beratan Temple as a Tourist Destination Area (DTA) located in Candikuning Village. The natural beauty of the surrounding causes tourist visits to increase every year. As a DTA, the area outside the Ulun Danu Beratan Temple is used as an arena for economic contestation for a multicultural community. There are several things that make the Ulun Danu Beratan Temple as an arena of economic contestation for a multicultural society such as natural beauty,